2017
DOI: 10.1016/j.ijpara.2016.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Fasciola hepatica demonstrates high levels of genetic diversity, a lack of population structure and high gene flow: possible implications for drug resistance

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
69
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 78 publications
(106 reference statements)
12
69
2
4
Order By: Relevance
“…3). The clonal lineage of the haplotypes in most of the F. gigantica populations is similar to the situation that has been described in F. hepatica (Beesley et al, 2017;Vilas et al, 2012) (Rana et al, 2014).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…3). The clonal lineage of the haplotypes in most of the F. gigantica populations is similar to the situation that has been described in F. hepatica (Beesley et al, 2017;Vilas et al, 2012) (Rana et al, 2014).…”
Section: Discussionsupporting
confidence: 79%
“…Our results confirm a high level of genetic diversity in F. gigantica (Table 2), implying the capacity for reproduction in the definitive host through meiosis during cross-breeding. A similar situation has been described in F. hepatica infection (Beesley et al, 2017;Vilas et al, 2012;Zintl et al, 2015). However, a low level of infection (Dar et al, 2011;Rondelaud et al, 2011) and clonal lineage in snails could give rise to a potential low population bottlenecking effect, raising questions about how genetic diversity might be maintained in F. gigantica.…”
Section: Discussionsupporting
confidence: 56%
“…We have shown that parasites with the same genotype tend to occur in the same animal giving evidence of clumped transmission and that clonal expansion occurs hence multiple genetically identical cercariae are likely to be released in a relatively small area (Beesley, Williams, Paterson, & Hodgkinson, ). However, there is little information on how far snails roam, or the distance cercariae travel once they exit the snail before encysting.…”
Section: Snail Biologymentioning
confidence: 99%
“…One of the main problems in anthelmintic resistance of this parasite is due to aspects of biology and population structure and pathogenicity, and the control of fascioliasis depends on genetic diversity (10,11). Both of these species may be identified by applying DNA sequences of nuclear ribosomal DNA internal transcribed spacers (ITS), and sequences of CO1 and ND1 as mitochondrial genes to analyze intraspecific phylogenetic relationship of Fasciola spp.…”
Section: Introductionmentioning
confidence: 99%